Improving the Productivity of Beef Heifers in Florida - John Arthington (EDIS, 2003)
This document is AN132, one of a series of the Animal Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date February 2003.